2023
DOI: 10.3390/w15203688
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Research Trends in Water Management Aimed at Increasing the Sustainability of the Socio-Economic Development of a Region

Zhanna Mingaleva,
Olga Chernova,
Inna V. Mitrofanova

Abstract: The growing negative anthropogenic impact on the environment causes scientific interest in the problems of water management. The increasing number of publications in this scientific field requires their intellectual systematization. The purpose of this study is to conduct a bibliometric review of scientific publications related to water management issues in the context of solving the problems of increasing the sustainability of the socio-economic development of a region for better understanding of current rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…This method has been widely adopted in diverse research fields to reveal current topic hotspots and research trends over time in specific research areas. It involves analyzing various metrics such as the number of annual publications, output of countries/regions, journals, total citations, citations per publication, and the Hirsch index [23]- [25]. Additionally, it enables the identification of research clusters and offers a comprehensive overview of the research field, thus providing a roadmap for further research.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been widely adopted in diverse research fields to reveal current topic hotspots and research trends over time in specific research areas. It involves analyzing various metrics such as the number of annual publications, output of countries/regions, journals, total citations, citations per publication, and the Hirsch index [23]- [25]. Additionally, it enables the identification of research clusters and offers a comprehensive overview of the research field, thus providing a roadmap for further research.…”
Section: Discussionmentioning
confidence: 99%
“…The nexus research pointed toward research on connecting sectors, with growth in a ention to the water-energy-food nexus (WEFN), but indicated challenges in moving from nexus thinking to action [21]. One review showed some 10,208 articles from 2012 to 2022, with emphasis on the WEFN and its intersectoral interactions and regional issues [22].…”
Section: Bibliometric Studies Relating To Iwrmmentioning
confidence: 99%
“…It is also a research method for assessing the productivity of authors, countries, and institutions by revealing their global distribution, collaboration, knowledge structures development trends [3,4], depth topics, citations, citation times, and keyword co-occurrence based on Web of Science (WoS) database. While many bibliometric studies have been carried out in different scientific fields such as medicine, computing, geography, environmental science, social science, water management, and animal sciences for different purposes (e.g., [3][4][5][6][7][8][9][10]), limited studies have been carried out in forestry (e.g., [11,12]). In addition, published papers related to seed orchards have not yet been subjected to bibliometric analysis.…”
Section: Introductionmentioning
confidence: 99%